Analysis of Digital Media Image Tampering and Forgery Control - Tang, Bin; Sun, Mengyao; Zheng, Haowen; Han, Haiyun; Jin, Yu (Transactions on Computer Science and Intelligent Systems Research, 2024)
In recent years, the continuous innovation of computer vision processing technology has greatly improved the quality of people's production and life, while the accompanying tampering risk has also gradually increased. There are frequent incidents of people with ulterior motives using computer image processing technology to tamper with digital media and falsifying and cheating others. This paper mainly analyzes the technology and method of digital media image tampering and forgery, the social harm caused by the resulting tampering risk, and puts forward the corresponding management countermeasures.